The Impact of Duolingo Application Training on English Teaching Competence of Teachers and Students' Learning Independence at SDN Konang 4 Pamekasan - Citra Siwi Hanayanti; Fujiono Fujiono (CV Litera Inti Aksara, 2025)
The advancement of technology in education presents significant opportunities to enhance the quality of teaching and learning. This article discusses the impact of Duolingo application training on teachers' teaching competence and students' independent English learning at SDN Konang 4 Pamekasan. This community service program involved 12 teachers and 20 students in a series of training sessions and mentoring activities aimed at integrating Duolingo into English language learning. The results showed an improvement in teachers’ competence in utilizing educational technology, as well as increased student motivation and independence in learning. Teachers successfully leveraged Duolingo’s features—such as listening, speaking, reading, and writing exercises—to create more interactive and engaging learning experiences. Students felt more motivated to learn independently through the gamified approach offered by the application.This training concluded that the use of the Duolingo application has a positive impact on the quality of English learning and is recommended for implementation in other schools facing similar challenges.